2023
DOI: 10.3390/jcm12093187
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Attainment of Low-Density Lipoprotein Cholesterol Goals in Patients at High Risk of Cardiovascular Disease Treated with High-Intensity Statins: The TERESA Study

Abstract: Despite steady improvements in cardiovascular disease (CVD) prevention, a scarce proportion of patients achieve the recommended LDL-C goals, even under high-intensity lipid-lowering therapy (LLT). Our study aimed to evaluate the attainment rate of LDL-C targets recommended by the 2019 European guidelines, and to characterize potential factors associated with LDL-C goal achievement and change patterns in LLT. We conducted a retrospective, observational study on patients treated with high-intensity atorvastatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Despite this, the percentage of patients whose LDL-C levels are within therapeutic targets is very low, including patients with a higher vascular risk [16][17][18]. Although several reasons have been proposed, it seems that underestimation of the risk, as well as an inadequate perception of actual LDL-C control, play essential roles, since they lead to insufficient intensification of lipid-lowering treatment, which is key to the improvement of these figures [17,21,85].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the percentage of patients whose LDL-C levels are within therapeutic targets is very low, including patients with a higher vascular risk [16][17][18]. Although several reasons have been proposed, it seems that underestimation of the risk, as well as an inadequate perception of actual LDL-C control, play essential roles, since they lead to insufficient intensification of lipid-lowering treatment, which is key to the improvement of these figures [17,21,85].…”
Section: Discussionmentioning
confidence: 99%
“…Several real-world studies in different countries demonstrated the comparative advantage of ezetimibe added to statins to reach LDL-C target levels [12][13][14][15]. In a Chinese retrospective cohort study of 1727 ASCVD patients, the addition of ezetimibe to a statin produced the achievement rates of LDL-C below 1.8 and 1.4 mmol/L over the first year, as high as 50.6 and 25.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They were treated with ezetimibe combined with atorvastatin (47.8%) or rosuvastatin (52.2%) in a high-intensity regimen. Despite these combinations, LDL-C below 1.4 mmol/L was not reached in about 70% of the participants [13]. The Korean retrospective study analyzed electronic medical records from 4252 patients treated between 2015 and 2017 in two tertiary care medical centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millions of these patients suffer from ASCVD and should be chronically treated with three basic drugs: acetylsalicylic acid (ASA), statins, angiotensin-converting enzyme (ACE) inhibitors in many cases; often also beta-blockers, cardioprotective and metabolic drugs [ 17 ]. Cardiovascular risk factors closely coexist, but arterial hypertension and hypercholesterolemia are undoubtedly among the most feasible to control with the use of adequately selected, modern drugs, well-tolerated by patients [ 18 , 19 ]. The most important reasons for poor control of these two factors on a population scale remain unchanged and can be mainly considered as:…”
Section: Struggle Formentioning
confidence: 99%